Trafficking and Sexual Exploitation of Minors: Prevention Strategies in the Bogotá Region - Díaz-Cruz, Paula-Cristina; Rodríguez-Lizarralde, Carolina (FLACSO - Sede Ecuador, 2022)
Human trafficking is a transnational crime that is mainly concentrated in the form of sexual exploitation. Most of the victims are women and girls. The objective of the article is to identify the prevention strategies against trafficking of children and adolescents identified in the actions of civil society organizations in the Bogotá region, Colombia. Based on the methods of the interview and the survey, with the consolidation of the information in an Organizational Capabilities Index matrix, a measurement is made, according to the strategies of national and international organizations, and the challenges for understanding the phenomenon. It is concluded that ignorance of the ways in which the human trafficking market operates and the lack of strategies that assume the impacts of these commercial and lucrative practices leaves organizations behind in the face of a crime that arises from structural socioeconomic inequalities and is constantly changing.